Physiological Impacts of Personal Protective Equipment on Health Care Workers - Anum Arif; Ahsin Manzoor Bhatti; Akhter Hussain; Mohammad Tariq; Osama Hadi; Syed Hashim Ali Inam (Universitas Airlangga, 2021)
Introduction: Since the outbreak of the Ebola virus, its design has constantly been evolving to serve the purpose of protection without hampering the efficiency. In a study conducted in 2019, before the advent of COVID 19, it was found that performing precarious laboratory or clinical works while wearing PPE involved various restrictions compared to the same work without PPE. The objective of this study is to identify the influence of personal protective equipment on physiological parameters and the individual wellbeing of healthy workers. Methods: This Pilot Quasi-experimental study was performed on 12 volunteers fitting the inclusion criteria. Candidates were seated comfortably and their baseline resting pulse rate, respiratory rate, oxygen saturation via pulse oximeter, blood pressure, and End-tidal CO2 were recorded via a portable monitor. All candidates were asked to wear a KN95 mask along with a 3 ply mask over it and wear anti-fog goggles. All the above-mentioned parameters were recorded again after five minutes of comfortable sitting and ten minutes of brisk walk. Result: Significant difference is found between resting EtCO2 and after wearing of PPE (P = 0 .044). After a brief exercise, the further rise in EtCO2 is also significant (P = 0.002). There is no significant rise in pulse after wearing PPE (P = 0.092) but on exertion after wearing PPE, the rise in pulse is statistically significant (P = 0.002). The rest of the variables, such as the rise in respiratory rate, blood pressure, and fall in oxygen saturation rise has no statistical significance. Conclusion: Personal protective equipment has proven to rise in end-tidal carbon dioxide and tachycardia, which can lead to headache, dizziness, and respiratory discomfort. All of the factors can hamper the health care workers' performance and can adversely affect their efficiency.Keywords: covid-19, end tidal CO2, personal protective equipment, physiological